The Identification of Weed Species Growing Around Eucalyptus pellita 6 Months Old:Case Study At PT. RAPP Estate Tesso Timur TEEB036 - Hutasuhut, Ika Lestari; Ervayenri, Ervayenri; Susilo, Trio Joko; Sadjati, Emy (Jurnal Penelitian Kehutanan BONITA, 2025)
Industrial plantation forests play a crucial role in the industry by focusing on the management of wood as a raw material. The Eucalyptus CEP 04 plants used in HTI at PT. RAPP Estate Tesso Timur require not only optimal growth but also careful attention to nutrient availability in the soil. Additionally, the presence of weeds under the main crop stands, such as Eucalyptus CEP 04, is an important factor in maintaining productivity. Thisresearch was conducted to identify the types of weeds found under the 6-month-old. Eucalyptus CEP 04 stands. Data collection occurred in areas with denser weed growth beneath these 6-month-old plants. The methodology used for data collection involved creating observation plots, with a total of six plots being established through purposive sampling. The results of the weed identification revealed nine different weed species, including Acacia (Acacia mangium), Sapat Kecil (Macaranga trichocarpa), Paku Resam (Dicranopteris linearis), Senduduk (Melastoma malabathricum), Teki-tekian (Pogonatherum crinitum), and Tenggek Burung (Melicope ptelefolia). The methods for controlling various types of weeds include manual techniques such as weeding, plucking, and thinning, effective chemical methods using herbicides, and combination approaches.